Whistleblowing and accounting for the public interest: a call for new directions. Issue 7 (13th July 2021) - Quayle, Annette
Abstract : Purpose: This paper aims to generate new research directions at the intersection of accounting, whistleblowing and publicness: defined as the attainment of public goals, interests and values. Design/methodology/approach: A problematising review is used to challenge and rethink the existing accounting and whistleblowing literature by incorporating readings from the public interest and public value literature. The paper draws on the work of Dewey (1927), Bozeman (2007) and Benington (2009) to open up new ways of theorising relations between accounting, whistleblowing and publicness. Findings: Firstly, the paper develops a public interest theoretical framework which shows whistleblowing is a public value activity that moves organisational wrongdoing into the public sphere where it is subject to democratic debate and dialogue required to reconcile the public's interests with what the public values. Secondly, this framework provides one answer to continuing questions in the literature of how to define accountings relationship to the public interest. Finally, the paper suggests this conceptual framework be used to stimulate debate on whether and how one should expand existing accounting and accountability knowledge boundaries to incorporate the broader social, political and moral concerns highlighted by whistleblowers acting in the public interest. Originality/value: Accounting and whistleblowing research has ignored the theoretical implications of whistleblowing in the public interest. The paper shows how accounting and accountability can respond to the challenges of a shifting and intangible public interest by providing a conceptual framework to guide current and future theoretical questions of how accounting is connected to the public interest.